Development of crosslinkable, thermoplastic polyurethanes for cardiovascular prostheses - Theron, Jacobus Petrus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Process Engineering))--University of Stellenbosch, 2006.